Mental Preparation of Students Preceding the Course - Florentin Alice (Sciendo, 2019)
In the preparation of"complete actors" only the technical aspects are not decisive, they will not only train them for the level of mastery. Aerobic exercises, forexample, can only play a part in recreation and muscular development, but when we talk about the scenic movement that uses actors' preparation, the situation changes; the future actor has to work out physical exercises by passing through the mental as well as the spiritual filter. Each student should think about how the exercises indicated by the teacher feel in their bodies, the reception may be different from the way the teacher / college actors / dancers experience the movement. In this context, the student is the only expert in what he likes to do with the movements indicated by the one in front of him, or what emotions are evoked when he experiences a choreographic phrase. This makes the study of acting or dance a form of art, and the difference is given by their inner experiences. the uniqueness of the body on the move."